5y-9=6y-4

Simple and best practice solution for 5y-9=6y-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y-9=6y-4 equation:



5y-9=6y-4
We move all terms to the left:
5y-9-(6y-4)=0
We get rid of parentheses
5y-6y+4-9=0
We add all the numbers together, and all the variables
-1y-5=0
We move all terms containing y to the left, all other terms to the right
-y=5
y=5/-1
y=-5

See similar equations:

| (1/2)k=3.2 | | 1.03^x=36 | | 4/3g+1/6=7/6 | | -5a+36=16 | | x+1/6= | | -6y=45 | | -30=5t | | (y-22)+y=72 | | 5=a-3.2 | | x^2-14x-12=4 | | -x^2+1=12 | | 9-5x=1-2 | | -0,66x^2-4,6x+6,56=0 | | -0,66x^2-4,6x+8,56=0 | | 100/12.5=v | | n−7=49 | | 3(2+x)-(2+x)=14 | | 3x-(2+x)=14 | | 6+6x-(2+x)=14 | | −2x+5=12 | | 1.7x0.5=5.25 | | 28,392.31-x=11,356.21 | | 9=n÷4 | | 9x+9=-7x+7 | | 3x2=21x-7=7 | | 8x-7+2x=4x+12-(x+30) | | 8x-7+2x-4x-12+x-30=0 | | 2x-135=x+23 | | 3(f+2)+9=13+5f | | 42-5t=57 | | 0.5x1.7=1.95 | | 4^3x=77.2 |

Equations solver categories